PalmCare: Smart Mobile Platform for Oil Palm Plantation Management - RAMESH, VESHAL; Nur Liyana Sulaiman (Applied Information Technology And Computer Science, 2025)
PalmCare is a mobile platform designed to address operational inefficiencies at Felda Mayam Plantation, a 10-acre oil palm plantation in Pahang owned by Mr. Arbaleesparan. The current manual processes for task management, worker performance monitoring, and harvest record-keeping rely on paper-based systems and spreadsheets, leading to delays and miscommunication. The objective of this project to design PalmCare using object-oriented approach, develop mobile application and test using User Acceptance Testing. By applying the Software Development Life Cycle Model, PalmCare built with Flutter and a PHP framework, Supabase for real-time database synchronization. Unified Modelling Language diagrams use for requirement modelling and the 3-tier Model-View-Controller architecture was applied. The overall average System Usability Scale mean score is 75.0 over 100, which indicates good usability where users generally find the system easy to use and efficient. The significance of this project to oil palm industry is improved productivity, cost savings, and sustainable plantation management.